Suzuki-Miyaura Cross-Coupling Reaction and Potential Applications - Ioannis D. Kostas (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Suzuki-Miyaura cross-coupling remains a powerful tool in organic synthesis for C-C bond formation and has various industrial applications, for example, the synthesis of pharmaceuticals and materials. Intensive research efforts are being made into finding ways of improving and expanding the scope of this process, and the development of more efficient catalytic systems for this extremely important reaction is still a hot research topic of enormous academic and industrial interest. This Special Issue, consisting of four reviews, two communications and six articles, focuses on recent promising research and novel trends in the broad field of Suzuki-Miyaura cross-coupling employing a range of different palladium catalysts. Homogeneous or heterogeneous catalysis in organic or aqueous medium, using conventional conditions or non-conventional techniques such as microwave and ultrasound irradiation, grinding and photo-activated processes as green chemistry approaches, as well as continuous flow technology are included. The catalysts described herein are unsupported metal complexes, catalysts immobilized on solid supports, ligand-free catalytic systems or metal nanoparticles.